Moslem Student Actualization in Instagram - Widaputri, Mazaya Conita; Novianti, Ida (International Conference of Moslem Society, 2018)
This article aims to examine and analyze self actualization of Muslim students in social media, instagram. This social media gives space to express the creativity, talents, and all the potential in each individual to develop themselves. The data of this study were explored through observation on 5 Muslim students who actively used instagram in the last month. Their posts will be studied through self-actualization theory of Abraham Maslow and tasawuf theory formulated by Suwito NS. The data in the form of posts from selected members will be analyzed through reading with the above theories. This study found that the self-actualization form of Muslim students in instagram tends to vary according to educational background, talents and interests, as well as motivation of Muslim students in their lives.